The Public Nature of Critical Discourses on “Religion” - MacKendrick, Kenneth G. (Method & theory in the study of religion, 2015)
Review Essay of William E. Arnal and Russell T. McCutcheon’s The Sacred is the Profane: The Political Nature of ‘Religion’ (Oxford: Oxford University Press, 2013).